MODÉL EXPLICIT INSTRUCTION PIKEUN NGARONJATKEUN KAMAMPUH NULIS TÉKS DRAMA: Penelitian Tindakan Kelas ka Siswa XII MIPA-2 SMA Negeri 1 Singaparna 2016/2017 - Roudloti, Selvia Awit (2017)
The Introduction of this research is about student's ability condition to write drama script in high school was poor and really need an attention. The problem faced by the students in writing the drama script is the student's usually felt really difficult to find an idea and convert it to the form of written language. In addition, when the student's wants to write a drama script, they often feel not really understand the elements of drama. In this case, the teacher has an important role in learning to write drama script. This study has a purpose to describe and analyze the learning plan of drama script writing using Explicit Instruction model in each cycle, and the result of write a drama text learning in each cycle. This study uses a Class Action Research method. The Techniques used in order to collect the data is observation technique and skill tests of the students. The source data of this research is students of class XII MIPA-2 on SMA Negeri 1 Singaparna. That sum 31 student's based on the research that has been conducted in two cycles, in planning step the research arrange the RPP and prepare point of observation, in process step there are four activities are planning, implementation, observation, and reflection. As for the results obtained in the pre-study 29,62% is 67.51 of KKM 75. In the first cycle, the result of the student that mastering the test as much as 62.96% with an average value of 75.66. But in the second cycle, the result increased to 100% with an average value of 80.66. The conclusion is that the teaching of drama script writing using a model of Explicit Instruction can improve students' skills in writing drama script. Keywords: Explicit Instruction Models, drama text's writing Latar belakang dari penelitian ini yaitu kurangnya kemampuan siswa dalam menulis teks drama. Permasalahan yang dihadapi siswa dalam menulis teks drama yaitu siswa kesulitan dalam menuangkan ide, gagasan dan belum memahami unsur-unsur drama. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis perencanaan, proses, dan hasil pembelajaran menulis teks drama menggunakan model Explicit Instruction dalam setiap siklus, penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK). Teknik yang digunakan dalam pengumpulan data yaitu teknik observasi, dan tes kamampuan siswa. Sumber data penelitian ini yaitu siswa kelas XII MIPA-2 SMA Negeri 1 Singaparna yang berjumlah 31 siswa. Berdasarkan penelitian yang telah dilakukan dalam dua siklus, pada tahap perencanaan peneliti menyusun RPP dan menyiapkan lembar observasi, pada tahap proses ada empat kegiatan yaitu tahap perencanaan, pelaksanaan, observasi, dan refleksi. Hasil yang diperoleh pada pra-siklus ketuntasan siswa sebanyak 29,63% dengan rata-rata nilai 67,51 sedangkan Kriteria Ketuntasan Minimal (KKM) yang ditetapkan yaitu 75. Pada siklus I ketuntasan siswa sebanyak 62,97% dengan rata-rata nilai 75,66. Dan, pada siklus II, ketuntasan siswa meningkat 100% dengan rata-rata nilai 80,66. Dengan demikian dapat disimpulkan bahwa pembelajaran menulis teks drama menggunakan model Explicit Instruction dapat meningkatkan kemampuan siswa dalam menulis teks drama. Kata Kunci: Model Explicit Instruction, menulis teks drama.